A cross-sectional pilot study to investigate diabetic knowledge and pharmaceutical care practice among registered and unregistered pharmacists in Iraq - Shaymaa Abdalwahed Abdulameer (Journal of Applied Pharmaceutical Science, 2018)
Pharmacists have crucial roles beyond dispensing medications. Hence, the present study aimed to assess the knowledge and pharmaceutical care practice towards diabetes mellitus (DM) among unregistered and registered community pharmacists in Iraq. An observational cross-sectional pilot study with a random cluster sampling method was carried out among registered and unregistered pharmacists in Baghdad. The study included three sections: the background and demographic information, diabetes knowledge test (DKT), and pharmaceutical care practice questionnaire. The mean total DKT, knowledge of general diabetes, and insulin use test subscales scores were 13.45 ± 3.36, 8.39 ± 2.22, and 5.06 ± 1.77, respectively, which revealed an inadequate knowledge. There were significant differences in the total DKT score with the university type and educational levels. Moreover, the diabetic care practice of the registered pharmacists were moderate (16.92 ± 4.28) and only 30.60% had positive practice. The highest and the lowest positive practice frequencies were found in blood glucose monitoring care (38.20%) and co-morbid DM disease management (21.20%), respectively. Furthermore, there were positive correlations between the total DKT and its subscales scores with the total diabetic care practice score. The results revealed that professional knowledge and practice toward DM among the sample population were inadequate. Hence, pharmaceutical care practices are a major concern in Iraq.
Keywords: Diabetes, Knowledge, Pharmaceutical care, Pharmacists, Practice.